2008
DOI: 10.1007/s11418-008-0243-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of the rhizomes of Alpinia officinarum on TPA-induced inflammation and tumor promotion in two-stage carcinogenesis in mouse skin

Abstract: The methanol extract of galangal (the rhizomes of Alpinia officinarum L.) exhibited remarkable antitumor-promoting activity on an in vivo two-stage carcinogenesis test of mice using 7,12-dimethylbenz[a]anthracene as an initiator and 12-O-tetradecanoylphorbol-13-acetate (TPA) as a promoter. Seven diarylheptanoids (1-7) were isolated and identified from the active fraction of the methanol extracts of the galangal. These compounds, 1-7, were evaluated for their inhibitory effects on TPA-induced inflammation (1 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…In a series of studies on the development of bioactive components from natural sources, we found that a methanol extract from the rhizome of Alpinia officinarum is effective in inhibiting tumor promotion in 12-O-tetradecanoylphorbol-13-acetate-induced inflammatory ear edema in mice [7]. Diarylheptanoids isolated from Alpinia officinarum have been shown to exhibit biological activities such as antioxidant activity [8,9], cytotoxic activity [10], suppressive activity of inducible nitric oxide synthase expression [11], and inhibitory activity of biosynthesis of prostaglandin and leukotriene [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies on the development of bioactive components from natural sources, we found that a methanol extract from the rhizome of Alpinia officinarum is effective in inhibiting tumor promotion in 12-O-tetradecanoylphorbol-13-acetate-induced inflammatory ear edema in mice [7]. Diarylheptanoids isolated from Alpinia officinarum have been shown to exhibit biological activities such as antioxidant activity [8,9], cytotoxic activity [10], suppressive activity of inducible nitric oxide synthase expression [11], and inhibitory activity of biosynthesis of prostaglandin and leukotriene [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A methanol extract of galangal inhibited TPAinduced tumor promotion DMBA/TPA in mouse skin. Seven diarylheptanoids were isolated from the methanol extract for inhibitory activity against TPA-induced inflammatory ear edema in mice (Yasukawa, et al, 2008). Fig.…”
Section: Galangal and Its Active Componentsmentioning
confidence: 99%
“…We isolated noble diarylheptanoid compounds from Alpinia officinarum [8,9] and demonstrated anti-tumor [9][10][11], anti-inflammatory [10], anti-influenza viral [12,13], and anti-RS virus properties [14,15]. In a subsequent study, we reported using translatome analyses to investigate the mechanisms and modes of action of these compounds [16].…”
Section: Introductionmentioning
confidence: 99%